Programmable Logic Controller (PLC) Based Paint Viscosity Control System - Gema Ridho Wicaksono; Riky Dwi Puriyanto (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
Automatic control has been developed in various fields, one of which is paint quality control. Paint quality can be controlled from various categories, including paint quality based on its viscosity. Therefore, we need a system that can control the viscosity of the paint. The paint viscosity control system uses the PLC OMRON CP1E-NA20DRA with a heater as a heat source, and the LM35DZ sensor as a temperature reading sensor, and the RPM reading is used to calculate the viscosity value. The programming language used is the ladder diagram on the CX-Programmer. This system uses the PID (Proportional, Integral, and Derivative) Algorithm so that temperature control can be set at 30ÂºC so as not to affect the viscosity of the paint. In addition, this prototype provides two PID tuning options, namely manual and auto-tuning. Researchers get the results that a good temperature control system response has a PB value = 0.2%; Ti = 452.5s and TD = 66.6s. and control the accuracy level of paint viscosity control of 67.82%.